2020
DOI: 10.1177/1077546320961918
|View full text |Cite
|
Sign up to set email alerts
|

Dual attention dense convolutional network for intelligent fault diagnosis of spindle-rolling bearings

Abstract: Over the past few years, deep learning–based techniques have been extensively and successfully adopted in the field of fault diagnosis. As the diagnosis tasks become more complicated, the structure of the traditional convolutional neural network (CNN) has to become deeper to deal with them, while the gradient of fault features may vanish within the deep network. In addition, all the features are treated equally in the traditional CNN, which cannot make the most of the representation power of CNN. Here, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The accuracy of the network predictions mentioned in these works are all greater than 93% [9,10,11,12,13]. DenseNet is widely used in other industrial fields, such as bearing fault detection [14]. DenseNet is also used in this work as an image classification method.…”
Section: 3densenetmentioning
confidence: 84%
“…The accuracy of the network predictions mentioned in these works are all greater than 93% [9,10,11,12,13]. DenseNet is widely used in other industrial fields, such as bearing fault detection [14]. DenseNet is also used in this work as an image classification method.…”
Section: 3densenetmentioning
confidence: 84%
“…Studies showed that the training time of traditional convolutional neural networks was too long, the accuracy was not ideal, and could not get diversified image features. Gradient dispersion would be generated in the process of backpropagation [42][43][44][45]. Based on these studies, we designed a multi-scale high-density convolutional neural network based on the multi-scale convolutional neural network and Densenet structure.…”
Section: H Performance Analysis Of Mhcnnmentioning
confidence: 99%
“…So as to realize automatic fault feature extraction and excellent diagnosis performance, the deep learning method has become a priority alternative. At present, due to its superior feature extraction ability and performance in classification task, lots of researchers apply deep learning method to bearing fault diagnosis [9], such as auto-encoder(AE) [10], deep belief network (DBN) [11],convolutional neural network (CNN) [12,13], etc. Among them, CNN is the most widely utilized to solve various complex problems in bearing fault diagnosis field, thanks to its flexible structure and less trainable parameters brought by weight sharing mechanism.…”
Section: Introductionmentioning
confidence: 99%